The independence of Miss Mary Bennet - McCullough, Colleen, 1937-2015.; Austen, Jane, 1775-1817. (New York : Simon & Schuster, 2008)
The best-selling author of The Thorn Birds presents a sequel to Pride and Prejudice that finds the willful third Bennet sister setting out in her late thirties in pursuit of adventure while her sisters worry about her at home.
Keywords: Social classes -- Fiction; Young women -- Fiction; England -- Social life and customs -- 19th century -- Fiction; Love stories; Regency fiction